There are no Sundays on the farm: A study on the Icelandic tradition of sending children to farms during the summer - Ólöf Daðey Pétursdóttir 1982- (2011)
Sending children to farms to live and work over the summer months in Iceland was a common custom in Iceland up until the late twentieth century. Children went from one week up to four months and went as young as five years old. In recent years there has been a tendency to classify traditions similar to the Icelandic farm tradition as child trafficking. The aim of this research is to look at the Icelandic tradition of sending children to farms and examine if the tradition can be classified as trafficking through the definition of trafficking found in the Palermo Protocol of 2000. The research was carried out in Iceland from January 2010 to February 2011. Data was collected using qualitative methods. The qualitative methods included formal and informal interviews. Individuals who experienced the tradition were interviewed. For the formal interviews the semi-structure interview form was chosen. Various reasons led to sending children to the farm over the summer time. Parents, farmers and children contributed to the decision making. Children experienced the farm stay in various ways, but farm life meant work and children experienced work on various levels. In most cases children experienced the work on the farms as a part of their upbringing while others felt they had been exploited. The tradition of sending children to farms over the summer months in Iceland should not be classified as trafficking. By looking at the Icelandic tradition of sending children to farms and examining it through the definition of trafficking found in the United Nation Trafficking Protocol of 2000, attention is brought to the fact that traditions similar to the ones experienced in the Western world in the near past, have been classified as trafficking and communities criminalized. By doing so the real victims of trafficking are focused on and anti trafficking measures will target the most vulnerable children in need of help. Key words: Trafficking, Palermo Protocol, recruitment, exploitation, child labor, child work, farm stay, Iceland.